1989
DOI: 10.1152/jappl.1989.66.3.1079
|View full text |Cite
|
Sign up to set email alerts
|

Taurine uptake by isolated alveolar macrophages and type II cells

Abstract: Evidence suggests that taurine may protect cellular membranes against oxidants (Gordon et al., Am. J. Pathol. 125: 585-600, 1986). The present study was conducted to determine if alveolar macrophages and type II cells (which are relatively resistant to oxidant injury) possess a specialized transport system for the accumulation of taurine. The results indicate that both cell types contain more taurine than plasma or whole lung. Taurine influx exhibited both carrier-mediated and simple diffusion components. Carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The configuration of the taurine uptake curve with a slow, gradual rise for 30 min followed by a plateau phase between 30 and 120 min is similar to the pattern observed in brain synaptosomes (14,15) and in intact cells such as type I1 alveolar pneumocytes (19). The different time course of taurine uptake in these systems versus renal brush border membrane vesicles, in which there is a rapid overshoot followed by a delayed equilibration (20)(21)(22), is probably due to inclusion of mitochondria within the synaptosomes (Figs.…”
Section: -Chd Chronic Hypernatremic Dehydrationsupporting
confidence: 70%
See 1 more Smart Citation
“…The configuration of the taurine uptake curve with a slow, gradual rise for 30 min followed by a plateau phase between 30 and 120 min is similar to the pattern observed in brain synaptosomes (14,15) and in intact cells such as type I1 alveolar pneumocytes (19). The different time course of taurine uptake in these systems versus renal brush border membrane vesicles, in which there is a rapid overshoot followed by a delayed equilibration (20)(21)(22), is probably due to inclusion of mitochondria within the synaptosomes (Figs.…”
Section: -Chd Chronic Hypernatremic Dehydrationsupporting
confidence: 70%
“…The sensitivity of synaptosomal taurine transport to these agents differed from renal brush border membrane vesicles (5,20,21), human placental membrane vesicles (27), isolated rat brain capillaries (28), or pulmonary macrophages and type I1 pneumocytes (19). The diminished inhibitory capacity of @-aminoisobutyric acid versus p-alanine and hypotaurine may occur because @-aminoisobutyric acid is sterically too large to compete with taurine for cerebral uptake (29).…”
Section: -Chd Chronic Hypernatremic Dehydrationmentioning
confidence: 99%
“…18,19 In pneumocytes, taurine uptake is dependent on extracellular sodium, and acute hypoxia impairs the sodium transport systems. 20,21 Taurine has cytoprotective properties and contributes to calcium homeostasis and the regulation of membrane structure and intracellular osmolality. 22 We demonstrated that taurine suppressed the hypoxic upregulation of S100C mRNA through, in part, the inhibition of HIF-1-dependent transcriptional activation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine is normally found in millimolar concentrations, especially in tissues that are excitable and generate oxidants. Active uptake of taurine by AM is sodium-and energy-dependent and can achieve an intracellular concentration of 4.27 mM (13). Studies have shown that intracellular taurine exists in a rapidly exchangeable free pool and in a slowly exchangeable bound pool (29).…”
Section: Mm-1cmi-resultsmentioning
confidence: 99%
“…Although not clear, the action of taurine has been attributed to its oxidantinhibitory and membrane stabilizing properties (11). Recent studies by Banks et al (12,13) indicate that there is an active uptake of taurine by alveolar macrophages that results in an inhibition of oxidative cell injury caused by ozone exposure. These results suggest that taurine may be used to study the potential relationships between intracellular oxidative events and the fibrotic process.…”
Section: Introductionmentioning
confidence: 99%